Contextual teaching and learning to improve conceptual understanding of primary students - Dita Ciptaningtyas Kristidhika; Wiputra Cendana; Ireremena Felix-Otuorimuo; Chris Müller (Research and Social Study Institute, 2020)
The learning capacity aims to bring multidimensional changes in human life aspects for the better. However, in the reality, both teachers and students struggle to carry out an effective learning process. Learning becomes meaningless which causes low conceptual understanding of students on what they learn. Contextual Teaching and Learning (CTL) is one learning model that can help students associate the lesson with their life context and make sense of things they learn. Therefore, this research aims to (1) elaborate on the significance of students’ conceptual understanding, and (2) elaborate on the effectiveness of CTL in improving conceptual understanding of primary students. The research method used is descriptive qualitative and the result shows that CTL is effective to help teachers carry out a meaningful learning experience to improve students’ conceptual understanding. It is recommended that (1) CTL can be implemented with various learning methods and media according to the learning environment and students’ characteristics, (2) apply CTL consistently in a period of time, and (3) manage the time well so all components in CTL can be performed as a whole.